HYGIENIC ASSESSMENT OF QUALITY OF ENVIRONMENT IN SHELEKHOV (IRKUTSK REGION) - A. N. Perezhogin; N. P. Safronov (Acta Biomedica Scientifica, 2013)
The aim of the research was to give an assessment of quality of environment and ensuring sanitary and epidemiologic wellbeing of the population of Shelekhov region. The research was conducted with use of data of municipal information fund of social-hygienic monitoring of Territorial Department of Administration of Rospotrebnadzor of Shelekhov, Shelekhov and Slyudanka regions during 2007-2011. Complex assessment of pollution of atmospheric air in ground layer was conducted by Ktotal index and Hazard index (HI). Upon the results of laboratory researches the assessment of pollution of soils in residential area of the city. Data of control of contents of fluorine, zinc, cadmium, lead and copper is used, total hazard is estimated with use of Ksoil index. The analysis of morbidity was conducted on the data of report form N 12. As the result of insufficient measures on the sanitary protection of water-supply sources low effectiveness of water-treatment the large part of drinking water samples that didn't meet the hygienic requirements was found: 2,5-3,7 % - based on the sanitary-chemical indices and about 3 % - based on the indices of microbiological safety. It was found that 100 % of soil samples didn't correspond to the claims of hygienic normative in fluorine contents. The territory of the city is characterized by the high level of air pollution with harmful admixtures of anthropogenic nature. The dust with silicon oxides and gaseous compounds of fluoride, benz(a)pyrene, sulfur dioxide, manganese, nitrogen oxides, carbonic oxide, formaldehyde were found to be priority chemical substances which may pollute atmospheric air. Respiratory organs, blood, eyes, immune and nervous systems were found to be the most loaded with the non-cancerogenic risk that may conform with actual data on the children's morbidity rate. During the period of 2003-2011 the morbidity rate of respiratory organs, blood, eyes as well as nervous systems was found to be higher in the children in Shelekhov than the average one in Irkutsk region. Thus the main role of formation of unfavorable environmental situation in Shelekhov was found to be associated with the pollution by hydrogen fluoride as well as by benz(a)pyrene. The environmental pollution and other unfavorable factors may significantly deteriorate the state of population health of the city.